Partnership for Healthier Rural Communities - Peg Lyons; Carolyn Crow; Linda Dunn; Becky Edwards; Ann Graves; Mitch Shelton; Jeri Dunkin (Rural Nurse Organization; Binghamton University, 2001)
The purpose of this project was to assess the health status of residents of a small rural community with limited health resources while providing a teaching-learning environment that increases students' knowledge and skills relative to nursing in a rural community. Twenty-two men, 45 women, and six children participated in a one-day health fair sponsored by a school of nursing. Results indicated that participants need assistance with health promotion in several areas: weight loss/obesity, blood sugar control, lowering cholesterol levels, vision and hearing follow-up, and further screening and possible treatment for depression. Students who conducted the health fair were asked to complete a short questionnaire examining their beliefs related to the usefulness of the health fair. Responses were generally positive; however, some students rated the health fair negatively. Recommendations are given for concentrated follow-up with the study participants as well as suggestions for increasing student assessment of the usefulness of this activity. Keywords: rural nursing, health fair, health promotion, nursing clinics, health risk appraisal http://dx.doi.org/10.14574/ojrnhcv2i2.467